2015
DOI: 10.1016/j.egypro.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diesel Engine Operating Conditions on the Particulate Size, Nanostructure and Oxidation Properties when Using Wasting Cooking Oil Biodiesel

Abstract: Present work focuses on the effect of engine operating parameters, including the engine speed and engine load (air/fuel ratio), on the particulate nanostructure and oxidative reactivity when the engine is operated with WCO (waste cooking oil) biodiesel. The particulate samples were collected from the diluted exhaust produced by a medium-duty direct injection diesel engine and were used to analyze the physical and chemical properties via using the high-resolution transmission electron microscope (TEM) and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The vertical distance between two parallel microcrystalline carbon layers is shown in Figure . Man's study showed that the oxidative reactivity of particulates is related to their nanostructure and that the interfacial layer strongly influences the oxidation activity of particulates . The increase in the interfacial layer thickness can increase the contact area of the oxygen reaction between the carbon microcrystalline layer and improve the oxidation activity of particulates.…”
Section: Resultsmentioning
confidence: 99%
“…The vertical distance between two parallel microcrystalline carbon layers is shown in Figure . Man's study showed that the oxidative reactivity of particulates is related to their nanostructure and that the interfacial layer strongly influences the oxidation activity of particulates . The increase in the interfacial layer thickness can increase the contact area of the oxygen reaction between the carbon microcrystalline layer and improve the oxidation activity of particulates.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that biodiesel leads to a reduction in HC, CO, and particulate mass concentration and number concentrations, but an increase in NO x . Man et al [27] studied the effect of diesel operating conditions on the particle size emitted by a diesel engine operating with WCO biodiesel. They found more particles with larger size at lower engine speed; primary particles tend to form at lower engine load.…”
Section: Introductionmentioning
confidence: 99%
“…Man et al. () studied the effect of engine speed and engine load (air/fuel ratio) on particulate nanostructure and oxidative reactivity when the engine was operated with WCO biodiesel. High‐resolution transmission electron microscope images revealed that larger primary particles were formed at low engine speeds and high engine loads when compared with diesel.…”
Section: Performance Of Biodiesel As a Fuelmentioning
confidence: 99%